Assessing the methodological quality of clinical guidelines for preventing falls of patients - Kamila Majkusová; Darja Jarošová; Renáta Zeleníková; Radka Kozáková (University of Ostrava, 2016)
Aim: The study aimed to assess the methodological quality of selected clinical practice guidelines (CPGs) for preventing risk of falling in adult patients in acute and long-term institutional care. Design: Descriptive study using qualitative research techniques. Methods: CPGs were systematically searched in databases of clinical guidelines, systematic reviews, electronic databases, and websites of organizations and professional societies, based on predefined criteria and keywords fo the period 2000-2015. After sorting and analysing 53 documents, the methodological quality of seven selected CPGs were assessed with the AGREE II generic instrument. Results: All CPGs obtained highest domain scores in the dimensions Clarity and Framework, and Purpose, while the lowest standardized scores were achieved by the Applicability and Editorial independence domains. The Rigor of development and Stakeholder Involvement domains achieved an average score. A total of three recommended guidelines showed high methodological quality: Falls. Assessment and prevention of falls in older people - 572 b., 84 % (NICE, 2013); Preventing Falls and Harm From Falls in Older People. Best Practice Guidelines for Australian Hospitals - 556 b., 84 % (ACSQHC, 2009); and Prevention of falls and fall injuries in the older adult - 559 b., 82 % (RNAO, 2005). Conclusion: Assessing the methodological quality of clinical guidelines using the AGREE instrument is one of the key steps in the process of their adaptation for other socio-cultural and organizational conditions. It would be possible to adapt and use all of the three most highly-rated CPGs to reduce risk of falling of inpatients in the Czech organizational and socio-cultural context.